KARAKTERISTIK MUTU MINYAK BIJI BINTARO (Cerbera manghas L) BERDASARKAN TINGKAT KEMATANGAN BIJI - Nurloviana, Sanggra; Sulaeman, Rudianda; Sribudiani, Evi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Bintaro plants grow naturally in Sumatera swamplands, yet people have not utilized this plant because of the lack of knowledge. Bintaro seeds have high oil content which makes it potential as a source of vegetable oil and can be developed as fuel too. The purpose of this research is to know the effect of different maturity level and treatment on the quality of bintaro seed oil content using soxhlet method with n-hexane solvent and also to determine the treatment process to obtain the best quality of bintaro seed oil. The research was conducted in Agricultural Processing Laboratory and Agricultural Product Analysis Laboratory of Faculty of Agriculture, Riau University of Pekanbaru from June to August 2017. From several parameters used, it was found that fruit maturity and extraction method had significant effect on free fatty acid content, iodine number, saponification number, peroxide number, and yield. However, the maturity and extraction methods have no significant effect on oil viscosity. High levels of fat and iodine number in bintaro seeds cause it potential to be developed into a source of vegetable oil.Finally, it is found that the best treatment for bintaro seed oil is by deriving it from 100% ripe fruit extracted using n-hexane solvent with yield of 52,93%, free fatty acid content 3,28%, iodine numberÂ  73.52 g I2 / 100 g, peroxide value 14.23 mg O2 / g, saponification value 203.67 mg KOH / g, and a viscosity value 63.28 cP.Keyword: Bintaro seeds, Soxhlet method, Free fatty acid, Saponification number, Viscosity.